2012
DOI: 10.1021/ja301509h
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Bound Molecular Rulers for Probing the Electrical Double Layer

Abstract: Herein, we report the first experimental investigation on the effect of varying the position of redox-active moieties, within the electrical double layer, on the apparent formal potential and on the electron transfer rate constant. This was achieved using a rigid class of molecules, norbornylogous bridges, to place redox species (ferrocene) at a fixed position above the surface of the electrode. Cyclic voltammetry and alternating current voltammetry were used to calculate the apparent formal potential and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 27 publications
4
46
1
Order By: Relevance
“…By changing the length of the diluent, the redox species are essentially moved through the Stern and diffuse portions of the electrical double layer. 5 In that previous study, we showed that SAMs composed of ω-hydroxyalkanethiol has a potential profile similar to that proposed for bare unmodified metal surfaces i.e. a steep drop in potential in the Stern layer followed by a smaller potential drop in the diffuse layer or the Gouy-Chapman layer which displays an approximately exponential decay in potential out to the bulk electrolyte.…”
Section: -Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…By changing the length of the diluent, the redox species are essentially moved through the Stern and diffuse portions of the electrical double layer. 5 In that previous study, we showed that SAMs composed of ω-hydroxyalkanethiol has a potential profile similar to that proposed for bare unmodified metal surfaces i.e. a steep drop in potential in the Stern layer followed by a smaller potential drop in the diffuse layer or the Gouy-Chapman layer which displays an approximately exponential decay in potential out to the bulk electrolyte.…”
Section: -Introductionsupporting
confidence: 71%
“…For instance, using conventional alkanethiol as the base layer of redox active monolayers, the redox species are located at the organic layer-solution interface, which is essentially within the electrical double layer. [3][4][5] In an electrochemical experiment, the redox active species will not feel the potential difference between the working electrode and the reference electrode but something in between as determined by the nature of the electrical double layer. The effect of the electrical double layer on surface-bound redox active groups was first proposed by the theory of interfacial potential distribution of Smith and White 3 and expanded by Fawcett.…”
Section: -Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such Fc-terminated SAM modified electrodes show a one-electron redox reaction: Fc ⇌ Fc + + e − . So far, many reports have been published on electron-transfer kinetics [5][6][7][8], electric double-layer effects [9,10], application as an electron mediator [11] and also biosensing [12][13][14]. In these studies, however, Fc moieties were usually exposed on the surface of SAM.…”
Section: Introductionmentioning
confidence: 99%